Penerapan Komunikasi Nonverbal: Sebuah Alternatif Dalam Peningkatan Perhatian Mahasiswa Pada Proses Pembelajaran - Muhammad Randicha Hamandia; Zhila Jannati (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2020)
Attention is an important element in the learning process. With attention, the learning process will be active and conducive. The effectiveness of the learning process in the classroom will be achieved if each student is able to achieve good attention so that explanations from lecturers or other students can be absorbed well to realize quality learning success. The purpose of this study is to find out how the application of nonverbal communication can be an alternative in increasing student attention in the learning process. The qualitative method is the method chosen in this study. The number of subjects taken in this study were 28 students of the Islamic Communication and Broadcasting Study Program UIN Raden Fatah Palembang. Data collection in this study uses observation and interview techniques. While the data analysis in this study is descriptive qualitative data analysis. From these results it can be concluded that nonverbal communication can be an appropriate alternative in increasing student attention in the learning process.